Photoelastic Analysis of Stress Distribution in Oral Rehabilitation - Leal Turcio, Karina Helga; Goiato, Marcelo Coelho [UNESP]; Gennari Filho, Humberto [UNESP]; Santos, Daniela Micheline dos [UNESP] (Lippincott Williams & Wilkins, 2009)
The purpose of this study was to present a literature review about photoelasticity, a laboratory method for evaluation of implants prosthesis behavior. Fixed or removable prostheses function as levers on supporting teeth, allowing forces to cause tooth movement if not carefully planned. Hence, during treatment planning, the dentist must be aware of the biomechanics involved and prevent movement of supporting teeth, decreasing lever-type forces generated by these prosthesis. Photoelastic analysis has great applicability in restorative dentistry as it allows prediction and minimization of biomechanical critical points through modifications in treatment planning.
Keywords: Photoelasticity; dentistry; implants